2008
DOI: 10.1088/0957-4484/19/17/175704
|View full text |Cite
|
Sign up to set email alerts
|

The coordinated buckling of carbon nanotube turfs under uniform compression

Abstract: Complex structures consisting of intertwined, nominally vertical carbon nanotubes (CNTs), referred to as turfs, have unique properties that arise from their complex nanogeometry and interactions between individual CNT segments. For applications such as contact switches for electrical or thermal transfer it is necessary to understand the properties that arise from the collective behavior of an assemblage of CNTs rather than the properties of a single tube. In this study, the mechanical response of turfs bonded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
98
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(106 citation statements)
references
References 25 publications
8
98
0
Order By: Relevance
“…We provide a microstructure-based motivation for such a phenomenological constitutive relation and use it to explore changes in structural response with nanotube volume fraction. The collective properties of carbon nanotubes in the form of vertically aligned carbon nanotubes (VACNTs) have been explored for applications ranging from micro-electromechanical system (MEMS) [1][2][3] to low temperature energy dissipating materials. [4][5][6] This has led to growing interest in developing an understanding of VACNT's mechanical response which is key for rational design and life cycle analysis.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…We provide a microstructure-based motivation for such a phenomenological constitutive relation and use it to explore changes in structural response with nanotube volume fraction. The collective properties of carbon nanotubes in the form of vertically aligned carbon nanotubes (VACNTs) have been explored for applications ranging from micro-electromechanical system (MEMS) [1][2][3] to low temperature energy dissipating materials. [4][5][6] This has led to growing interest in developing an understanding of VACNT's mechanical response which is key for rational design and life cycle analysis.…”
mentioning
confidence: 99%
“…[4][5][6] This has led to growing interest in developing an understanding of VACNT's mechanical response which is key for rational design and life cycle analysis. [1][2][3]5,[7][8][9][10][11][12][13] VACNT materials are complex, hierarchical, and largely disordered assemblies of carbon nanotubes (CNTs) aligned nominally vertically with respect to the growth substrate. Experimental investigations have found that VACNTs have mechanical energy dissipative properties, 4,5,7,10 can exhibit high recoverability after large strains, 8,14,15 and deform via a sequential periodic buckling mechanism under uniaxial compression.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Other differences between these nominally identical VACNT samples are the ability of some of them to recover almost completely after large compressions (Figs. S1a and c) while others deform permanently even at modest strains [7][8][9][10][11] (Figs. S1b and d).…”
Section: Compressive Behavior Of Vertically Aligned Carbon Nanotube (mentioning
confidence: 99%